CAREER PATHWAYS IN ENTREPRENEURSHIP: HOW SELF-EFFICACY INFLUENCES ENTREPRENEURIAL INTENTIONS IN VOCATIONAL EDUCATION - Rafli, Muhammad; Hambali, IM; Muslihati, Muslihati (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
This study aims to analyze the relationship between career entrepreneurial self-efficacy and entrepreneurial intention among vocational high school students, as well as to identify factors supporting the development of entrepreneurship programs in vocational schools. The research method used a quantitative approach with a questionnaire adapted from the entrepreneurial intention and entrepreneurial self-efficacy scales, involving 276 vocational high school students in Malang City. Data were analyzed using descriptive statistical tests, confirmatory factor analysis (CFA), and Pearson correlation with the assistance of JASP and SPSS software. The results of the study indicate that vocational high school students have a fairly high level of entrepreneurial intention, with behavioral control perception as the most dominant aspect. Career entrepreneurial self-efficacy is also relatively high, particularly in human resource management and business planning. Correlation analysis revealed a significant positive relationship between career entrepreneurial self-efficacy and entrepreneurial intention, although other factors also influence this relationship. These findings emphasize the importance of strengthening students' self-confidence through integrated entrepreneurship programs, including financial literacy training, mentor guidance, and industry collaboration. This study recommends the development of a more comprehensive entrepreneurship learning model in vocational schools, considering affective aspects, practical skills, and ecosystem support to produce graduates who are ready to become entrepreneurs.